The Power of Circumstantial Evidence in the Trial Process The Crime of Murder - Dessy Adhya Purwandiny; Rendy Erianto Jullyan; Irwanda Imawan (Dinasti Research, 2025)
This research explores the power of circumstantial evidence in proving murder offences, focusing on the case of Jessica Kumala Wongso. In this case, despite the absence of direct evidence, elements such as CCTV footage, the motive of the accused, as well as forensic evidence played an important role in building the case against the accused. Using a normative juridical method and a case study approach, this research analyses the role and relevance of circumstantial evidence in Indonesian criminal procedure law. The results show that, although circumstantial evidence has significant power, its assessment must be done carefully and logically by the judge to avoid mistakes that can be detrimental to justice for the defendant. The Jessica Wongso case emphasises the importance of a coherent and integrated pattern of evidence, in order for the court to ensure that its decisions are based on in-depth analysis and not mere assumption.